To analyze and use the parameters in post-operative unstable intertrochanteric fractures treated using dynamic hip screw fixation as guidelines for re-operation - Aathipan, K. Thirusenthil; Ashok, T. R.; Ram, Ganesan G. (International Journal of Research in Orthopaedics, 2016)
Background: The treatment of unstable intertrochanteric fractures is challenging due to the difficulty in obtaining anatomical reduction. The purpose of this study was to analyse and use the parameters (lateral femoral wall integrity and tip-apex distance) in post-operative unstable intertrochanteric fractures treated using dynamic hip screw (DHS) fixation as guidelines for re-operation. Methods: This was a prospective study and included 40 patients with unstable intertrochanteric fractures treated using DHS fixation from December 2014 to September 2016. The AO/OTA classification was used to classify each of the patients and their lateral femoral wall integrity and tip-apex distance was assessed in the post-operative radiographs. Results: In this study, 3 patients out of 40 (7.5%) had screw pull out within 5 months of surgery. 2 pull outs occurred when the screw was in the antero-superior zone and 1 when it was in the centre to centre zone. Thus, the rate of screw pull out was higher in the antero-superior zone. The 3 patients with screw pull out had a mean tip-apex distance (TAD) of 36.01 mm as compared to 32.96 mm of those who did not have screw pull out. We further found that pre-operatively 6 patients out of 40 (15%) had lost lateral femoral wall integrity whereas post-operatively 26 patients out of 40 (65%) had lost it. In summary, there is a 5 times higher risk of losing lateral femoral wall integrity if DHS is the implant of choice. Conclusions: On conclusion, unacceptable TAD limit with loss of lateral femoral wall integrity was found to be a definite indicator of DHS implant pull out. And also found that by using the DHS as an implant of choice, there is a 5 times higher risk of losing lateral femoral wall integrity intra-operatively and that its use for the treatment of unstable intertrochanteric fractures must be guarded.